Noc Muzeów w bibliotece medycznej - Seiffert, Justyna (Biblioteka Uniwersytecka w Poznaniu, 2018)
Organizacja wydarzeń kulturalnych w bibliotekach to domena głównie bibliotek publicznych, rzadziej naukowych. Coraz więcej jednak bibliotek naukowych, w tym akademickich, decyduje się w ten sposób poszerzyć grono odbiorców. Biblioteka Śląskiego Uniwersytetu Medycznego w Katowicach (SUM) podjęła wyzwanie zorganizowania Nocy Muzeów. To właśnie budynek, w którym jest jej siedziba, oraz jego ciekawa historia pokazują skomplikowane dzieje Śląska i Ślązaków, jak również losy awangardy na Śląsku. Noc Muzeów w Bibliotece SUM z jednej strony nawiązuje do historii, z drugiej przybliża szerokiej publiczności zawartość gromadzonych przez książnicę zbiorów. Prezentuje tematykę medyczną w sferze zarówno edukacyjnej, jak i naukowej.

Academic libraries are less likely than public libraries to organize cultural events. Nevertheless some of them try to expand their influence by this mean. Library of Medical University of Silesia (SUM Library) took challenge to organize Night of Museums due to the historic building in which it is located. The building shows fascinating and complicated history of Silesia region and its inhabitants, as well as regional pursuit of being in the avant-garde. Night of Museums in SUM Library aimed to connect past and present, to encourage public health education and to show broad audience that Library’s building and its collections are open for everyone. In the city environment we are now a new point of cultural events during the annual Night of Museums. SUM Library also became more familiar for Silesia citizens and is seen as not only academic.
Night of Museums in academic medical library
Keywords: Noc Muzeów; Night of Museums; biblioteki akademickie; biblioteki medyczne; działalność kulturalna; cultural events in libraries; współpraca z instytucjami kultury; non health-related visitors